Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1002/hed.26617
|View full text |Cite
|
Sign up to set email alerts
|

Opioid reduction in ambulatory thyroid and parathyroid surgery after implementing enhanced recovery after surgery protocol

Abstract: Background Opioid abuse is widespread in the United States and the risk for chronic use is increased in surgical patients, including patients with thyroid and parathyroid. Methods Records for 171 patients prior to and 67 patients following implementation of an enhanced recovery after surgery (ERAS) protocol for ambulatory thyroid/parathyroid surgeries were reviewed. The ERAS included superficial cervical plexus block, multimodal premedication, and postoperative reliance on acetaminophen and ibuprofen with judi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…20 ERAS implementation often involves patient education, preoperative administration of non-opioid analgesia and anti-emetics, and judicious use of postoperative narcotics. 20,21 In our study, we found that only 11.2% of patients used ibuprofen postoperatively. Given the understanding that ibuprofen is a safe and valuable analgesic option, a formalized policy, such as an ERAS protocol, could serve to educate patients and improve usage rates.…”
Section: Discussionmentioning
confidence: 57%
“…20 ERAS implementation often involves patient education, preoperative administration of non-opioid analgesia and anti-emetics, and judicious use of postoperative narcotics. 20,21 In our study, we found that only 11.2% of patients used ibuprofen postoperatively. Given the understanding that ibuprofen is a safe and valuable analgesic option, a formalized policy, such as an ERAS protocol, could serve to educate patients and improve usage rates.…”
Section: Discussionmentioning
confidence: 57%
“…There is limited data on the role of ERAS in our study population. Two publications examined the role of ERAS in decreasing opioid use following PTX [ 12 13 ], but these studies did not distinguish primary hyperparathyroidism from SHPT. To the best of our knowledge, this is the first study to evaluate the role of an ERAS program in reducing the incidence of HBS among patients on hemodialysis who underwent PTX [ 12 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Two publications examined the role of ERAS in decreasing opioid use following PTX [ 12 13 ], but these studies did not distinguish primary hyperparathyroidism from SHPT. To the best of our knowledge, this is the first study to evaluate the role of an ERAS program in reducing the incidence of HBS among patients on hemodialysis who underwent PTX [ 12 13 ]. Patients on hemodialysis for ESRD have an increased risk for electrolyte imbalances, and previous studies demonstrated an association between renal impairment and hemodialysis and readmission after PTX [ 21 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the use of dexmedetomidine during overnight thyroidectomy did not reduce the incidence of PONV at 24 hours in postoperation (p=0.355) ( 24 ). To reduce the incidence of the postoperative POVN, intraoperative cervical plexus anesthesia block, rational use of anesthetic drugs in preoperative multimodality, postoperative use of non-steroidal drugs such as Acetaminophen or Ibuprofen in combination with appropriate Opioid analgesia has a good effect on preventing postoperative POVN, which can also indirectly reduce the dosage of opioids ( 25 ). Therefore, anesthesiologists should consider more factors in the choice of anesthesia drugs and anesthesia methods and choose the types of drugs and anesthesia methods more carefully.…”
Section: The Associated Complicationsmentioning
confidence: 99%